High-operating-temperature infrared photodetectors - Piotrowski, Jozef, 1943- (SPIE, 2007)
This book presents approaches, materials, and devices that eliminate the cooling requirements of IR photodetectors operating in the middle- and long-wavelength ranges of the IR spectrum. It is based mainly on the authors' experiences in developing and fabricating near room temperature HgCdTe detectors at Vigo Systems Ltd. and at the Institute of Applied Physics Military University of Technology (both in Warsaw, Poland). The text also discusses solutions to other specific problems of high-temperature detection, such as poor collection efficiency due to a short diffusion length, the Johnson-Nyquist noise of parasitic impedances, and interfacing of very low resistance devices to electronics. Suitable for graduate students in physics and engineering who have received a basic preparation in modern solid state physics and electronic circuits, this book will also be of interest to individuals who work with aerospace sensors and systems, remote sensing, thermal imaging, military imaging, optical telecommunications, IR spectroscopy, and lidar.
"SPIE digital library."
Keywords: Infrared detectors.; Optical detectors.; elektronické knihy; electronic books